Treatment of Staphylococcus aureus endocarditis in rats with coumermycin A1 and ciprofloxacin, alone or in combination. - Perronne, C M (1987)
The efficacy of a 5-day treatment with coumermycin A1 (hereafter referred to as coumermycin) (at three dosage regimens), with ciprofloxacin, or with coumermycin plus ciprofloxacin was tested in experimental aortic valve endocarditis induced in rats by a strain of methicillin-susceptible Staphylococcus aureus and was compared with the efficacy of a 5-day treatment with cloxacillin plus gentamicin. While coumermycin was far less effective than cloxacillin plus gentamicin in reducing the bacterial counts in vegetations (P less than 10(-8), ciprofloxacin was as effective as cloxacillin plus gentamicin. Coumermycin plus ciprofloxacin was less effective than ciprofloxacin alone (P = 0.01). For endocarditis induced by two additional methicillin-susceptible S. aureus strains, the high-dosage regimen of coumermycin (12 mg/kg every 12 h) had the same low efficacy. Coumermycin-resistant variants of S. aureus emerged in most of the vegetations during coumermycin treatment. The ciprofloxacin susceptibility of S. aureus was unchanged during ciprofloxacin treatment. The addition of ciprofloxacin to coumermycin in the treatment did not prevent the emergence of coumermycin-resistant variants. Twelve additional S. aureus strains isolated from the blood of patients with endocarditis were tested in vitro against coumermycin with precautions to avoid carry-over of the antibiotic. Coumermycin exhibited a bacteriostatic activity at very low concentrations (MIC, less than 0.004 microgram/ml) but only a weak bactericidal activity (MBC for 90% of strains, 8 micrograms/ml), a finding contrasting with that of others. Furthermore, coumermycin-resistant mutants could be selected in vitro from the 15 S. aureus strains tested. These results indicated no evidence in vivo of a synergistic activity of coumermycin and ciprofloxacin. More importantly, these results suggested that coumermycin might not be adequate for the treatment of serious s. aureus infections in humans.